2014
DOI: 10.1155/2014/386920
|View full text |Cite
|
Sign up to set email alerts
|

A New Wideband Mutual Coupling Compensation Method for Adaptive Arrays Based on Element Pattern Reconstruction

Abstract: A new mutual coupling compensation method for wideband adaptive arrays is proposed. The new method is developed by combining the element pattern reconstruction method and the system identification method. The element pattern reconstruction method is valid and effective in the mutual coupling compensation for adaptive arrays such as dipole arrays and microstrip arrays. Each entry of the wideband compensation matrix is represented as an analytical expression against frequency. The polynomial coefficients and ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The frequency bandwidth of the isolated element covers about 2.25 octaves with VSWR ≤ 2.2. Besides, the center frequency is 368.5 MHz, and the relative bandwidth reaches 78%, which is much more than the relative bandwidth in previous methods [14,15]. The VSWR of the array state is terrible compared with that of the isolated state, which shows that the performance of the array is deteriorated by the mutual coupling of the antenna elements.…”
Section: Wideband Monopole Antenna and Arraymentioning
confidence: 89%
See 2 more Smart Citations
“…The frequency bandwidth of the isolated element covers about 2.25 octaves with VSWR ≤ 2.2. Besides, the center frequency is 368.5 MHz, and the relative bandwidth reaches 78%, which is much more than the relative bandwidth in previous methods [14,15]. The VSWR of the array state is terrible compared with that of the isolated state, which shows that the performance of the array is deteriorated by the mutual coupling of the antenna elements.…”
Section: Wideband Monopole Antenna and Arraymentioning
confidence: 89%
“…It is shown that various feature points are chosen corresponding to different curves. The curve fitting represents the complex-curve fitting method which was employed in [14,15]. Three interpolation methods are compared, of which the Cubic is the method employed in this paper; the Linear is the linear interpolation; the Spline is the cubic spline interpolation.…”
Section: Wideband Mutual Coupling Compensationmentioning
confidence: 99%
See 1 more Smart Citation
“…The technique combines interferometry and a modified multiple signal classification (MUSIC) method to mitigate mutual coupling effects. In [20,21], narrowband MCMs at some discrete frequencies are calculated firstly based on the receiving mutual impedance method or the element pattern reconstruction method, then, utilizing the system identification methods, a wideband calibration matrix is obtained, which can be used to compensate the mutual coupling effects at all frequencies. An analysis of wideband DOA estimation taking account of mutual coupling effects is presented in [22,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Wang's method is also more suitable for the arrays composed of wire elements. An improved wideband mutual coupling calibration method was introduced to cover more element structures [10]. The 978-1-4673-65 44-4/15/$31.00 ©2015 IEEE element pattern reconstruction and complex curve-fitting are combined in this method [7,II].…”
Section: Introductionmentioning
confidence: 99%